Structure and enhanced electromagnetic properties of Y3+ substituted microwave sintered NiZnCo ferrites. Issue 3 (1st February 2021) - Wu, Xiao-Hui; Li, Le-Zhong; Wu, Bo; Zhong, Xiao-Xi; Wang, Rui; Tu, Xiao-Qiang; He, Lei; Zou, Chen-Yu; Hou, Bo-Ren
Abstract: Ni0 6 Zn0 . 3 Co0.1 Y x Fe2- x O4 ferrites (0 ≤ x ≤ 0.1) were fabricated by a sol–gel autocombustion method using Microwave Sintering Technology (MST) and Conventional Sintering Technology (CST). With increased Y 3+ ions, the structure and electromagnetic performance of all MST samples were better than those of CST. In addition, the MST and CST samples formed a second phase (YFeO3 ) when x > 0.025 because the radius of the Y 3+ ion is larger than that of the Fe 3+ ion. Compared with the CST samples, the MST samples showed increased densification and average grain size. Meanwhile, excellent electromagnetic performance of MST was achieved when the amount of Y substitution was 0.025, with high saturation magnetization ( M s, 154.19 emu/g), the lowest coercivity ( H c, 20.21 Oe), the lowest dielectric constant ( ε ′, 10.82@1 MHz), lower dielectric loss (tanδ, 0.0093@1 MHz) and the highest direct-current resistivity ( ρ, 2.706 × 10 6 Ω⋅m). These excellent results also confirm the good prospects of microwave sintering, which can better meet the needs of modern electronic devices for high frequency and low loss.